Development and evaluation of a re-sequenced intervention module in learning chemical bonding - Asequia, Baby Eve N.; Alia, Leemarc C.; Matutes, Kevin Client B. (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the typical high school chemistry curriculum, chemical bonding precedes the chemical reactions. In this study, the re-sequenced effect of learning chemical bonding when chemical reactions are introduced first among grade 9 learners was investigated. A learning module with re-sequenced intervention in chemical bonding was developed using analysis, design, development, implementation, evaluation (ADDIE) model and validated by eight science education professionals rated as very satisfactory. A quasi-experimental research design was utilized in the implementation phase with 129 respondents selected through cluster random sampling. Pre- and post-tests, formative and summative assessments, and evaluation surveys were administered. Evaluation results revealed that the scores from the re-sequenced intervention group displayed a slightly higher overall satisfaction percentage (99.06%) compared to the control group (94.74%). In addition, the experimental group achieved significantly higher competency levels (M=49.3, SD=19.4) compared to the control group (M=41.4, SD=15.3), with p=0.016 and d=0.37. Furthermore, students reported positive perceptions despite initial misconceptions. These findings highlight that re-sequencing topic order enhances chemistry learning outcomes and student engagement. Hence, the re-sequenced learning module became a valuable tool for enhancing understanding of chemical bonding, independent of baseline competency or attitudes toward the material.